Kullback-Leibler Divergence of Mixture Autoregressive Random Processes via Extreme-Value-Distributions (EVDs) Noise with Application of the Processes to Climate Change. Issue 1 (2022) - Olanrewaju, Rasaki Olawale; Waititu, Anthony Gichuhi; Abiodun, Nafiu Lukman
No abstract available